Peran Praktik Lingkungan, Sosial dan Tata Kelola (ESG) dan Tanggung Jawab Sosial Perusahaan (CSR) terhadap Perilaku Karyawan di Perusahaan Energi - Eka Kurnia Arief Sukaryadi; Agus Suroso; Enny Dwi Cahyani (Jurnal Akuntansi, Manajemen dan Ekonomi, 2025)
This research explores the complex role of Environmental, Social and Governance (ESG) and Corporate Social Responsibility (CSR) practices in shaping employee behavior in the energy sector. Through a systematic literature review approach of research spanning 2017-2025, the study identifies the multidimensional dynamics through which sustainability initiatives influence employee motivation, engagement and performance. Key findings show that environmental dimensions are positively correlated with employees' intrinsic motivation, especially in the younger generation who show higher responsiveness to sustainability initiatives. Social aspects of ESG play a significant role in building emotional connectedness between employees and the organization, while transparent governance practices increase trust, encourage innovative behavior, and strengthen organizational citizenship behavior. The research shows significant variations in ESG implementation and impact across different energy subsectors, underscoring the need for an integrated contextual approach. The study concludes that the authentic integration of ESG and CSR practices not only improves financial performance and competitive advantage, but also fundamentally transforms the work ecosystem through the creation of a more meaningful, sustainable and competitive environment. The strategic implications suggest that ESG is increasingly becoming a key determinant in shaping employee behavior in the energy sector, emphasizing the importance of adopting a holistic approach that harmonizes business, employee, and environmental interests to create sustainable shared value.